Ms. Mentor's New and Ever More Impeccable Advice for Women and Men in Academia - Toth, Emily (Book collections on Project MUSE., 2009)
"Ms. Mentor, that uniquely brilliant and irascible intellectual, is your all-knowing guide through the jungle that is academia today. In the last decade Ms. Mentor's mailbox has been filled to overflowing with thousands of plaintive epistles, rants, and gossipy screeds. A mere fraction has appeared in her celebrated monthly online and print Q & A columns for the Chronicle of Higher Education', her readers' colorful and rebellious ripostes have gone unpublished - until now." "From the ivory tower that affords her an unparalleled view of the academic landscape, Ms. Mentor dispenses her perfect wisdom to the huddled masses of professorial newbies, hardbitten oldies, and anxious midcareerists. She gives etiquette lessons to academic couples and the tough-talking low-down on adjunct positions. She tells you what to wear, how to make yourself popular, and how to decode academic language. Raw, shocking, precise, clever, absurd - Ms, Mentor has it all."--Jacket.